Karakteristik pasien cedera kepala di Rumah Sakit Umum Daerah (RSUD) Umbu Rara Meha Waingapu periode 1 Januari 2017 – 31 Desember 2018 - Made Bhuwana Putra (Intisari Sains Medis, 2019)
Background: Traumatic Brain Injury is among the leading causes of mortality and morbidity in the world, with the increase of incidence rate every year especially in the developing country concomitant with the rise in motor vehicle usage. In Indonesia, although the number is high, the study concerning the incidence and characteristic of patients with traumatic brain injury are still limited. This study has objective to show the characteristic pattern of traumatic brain injury cases at Umbu Rara Meha general hospital that, as the biggest hospital in Sumba Island, can be the representative for the area.Method: This study is a descriptive study with a retrospective design using the medical record in Umbu Rara Meha general hospital from January 1st until December 31th as secondary data. A non-probability sampling technique using consecutive was conducted. Data were analyzed using SPSS version 25 and depicted in mean, median, frequency, and percentage. Result: A total of 186 cases was included and from there it is shown that the highest prevalence rate of traumatic brain injury was in males (67,7%), and was dominated by the adolescence group (25,3%), although by occupation the highest rate was farmer and fisherman (32,3%). The leading cause of traumatic brain injury is an accident (82,2%) with mild traumatic brain injury (67,7%) as the most frequent type of severity. The average length of stay for traumatic brain injury was two days.Conclusion: The high number of the incidence rate of traumatic brain injury mainly from the accident and on adolescence group can be used as a reference for the local government or related institution to look more carefully about the awareness of safe driving or riding among the society and can be implemented through a program or other governing instrument.